PENGARUH JIWA ENTREPRENEUR TERHADAP PENJUALAN PRODUK UKM (KASUS PEDAGANG KONVEKSI PASAR AUR KUNING BUKITTINGGI) - Mardhiana Sari; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Industrial development is a change from an industrial organisasai or business entity which was originally small in a specified period turned into a huge industry in which the entrepreneur is required to make it happen.The existence of entrepreneurs engaged in small industries supporting Indonesian state economy that has not moved forward and thrive . through training and implementation of the entrepreneurial spirit is a small industry will be able to experience the business development on a larger scale gradually . This research aims to identify and analyze the entrepreneurial spirit that has been applied by traders convection aur kuning market . The sample 94 respondents. Data obtained through observation and questionnaires is measured using a Likert scale . Data were analyzed using descriptive statistical method to test equipment SPSS version 16 . The results of this study indicate that there is a significant relationship between the entrepreneurial spirit of the UKM product sales trader convection aur kuning market with a level of correlation equal to 33.2 %, which indicates strong criteria . Keyword : Entrepreneur Spirit, Development of Small Industries, Traders Convection